My paper has been rejected without review. What do I do now? - Cleland, Jennifer (2023)
This column is intended to address the kinds of knotty problems and dilemmas with which many scholars grapple in studying health professions education. In this article, the authors address the question of why papers may be desk rejected (rejected without going out for formal peer review) and describe simple steps for authors to optimize their work so it gets past the desk reject stage.